Aldose reductase inhibitor protects mice from alcoholic steatosis by repressing saturated fatty acid biosynthesis. (1st May 2018) - Guo, Chang; chen, Lizhu; Huang, Jie; Wang, Yuanfang; Shi, Changxuan; Gao, Jing; Hong, Yannv; Chen, Tong; Qiu, Longxin
Abstract: Alcoholic liver injury results in morbidity and mortality worldwide, but there are currently no effective and safe therapeutics. Previously we demonstrated that aldose reductase (AR) inhibitor ameliorated alcoholic hepatic steatosis. To clarify the mechanism whereby AR inhibitor improves alcoholic hepatic steatosis, herein we investigated the effect of AR inhibitor on hepatic metabolism in mice fed a Lieber-DeCarli liquid diet with 5% ethanol. Nontargeted metabolomics showed carbohydrates and lipids were characteristic categories in ethanol diet-fed mice with or without AR inhibitor treatment, whereas AR inhibitor mainly affected carbohydrates and peptides. Ethanol-induced galactose metabolism and fatty acid biosynthesis are important for the induction of hepatic steatosis, while AR inhibitor impaired galactose metabolism without perturbing fatty acid biosynthesis. In parallel with successful treatment of steatosis, AR inhibitor suppressed ethanol-activated galactose metabolism and saturated fatty acid biosynthesis. Sorbitol in galactose metabolism and stearic acid in saturated fatty acid biosynthesis were potential biomarkers responsible for ethanol or ethanol plus AR inhibitor treatment. In vitro analysis confirmed that exogenous addition of sorbitol augmented ethanol-induced steatosis and stearic acid. These findings not only reveal metabolic patterns associated with disease and treatment, but also shed light on functional biomarkers contribute to AR inhibition therapy. Graphical abstract: Highlights: Hematoxylin and eosin stains revealed aldose reductase inhibitor improved ethanol-induced steatosis. GC/MS method was developed for quantifying mouse liver metabolites. Ethanol induced lipid synthesis and carbohydrate metabolism. Aldose reductase inhibitor reduced saturated fatty acid biosynthesis and galactose metabolism. Stearic acid and sorbitol were potential biomarkers responsible for disease and therapy.